Examining the Predictors of SME Recovery in Severe Financial Distress: Insights from Literature on Financial Blockages, Employee Dynamics, and Turnaround Success - Yessica Amelia; Ngadi Permana (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This qualitative literature review examines the key predictors of SME recovery from severe financial distress, focusing on financial blockages, employee dynamics, and turnaround success. The study synthesizes findings from various sources to highlight how financial challenges such as liquidity shortages and limited access to credit hinder recovery, while government support and alternative financing offer potential solutions. Additionally, employee engagement, organizational culture, and strategic leadership are identified as critical factors in successful turnaround efforts. SMEs that foster innovation, adaptability, and retain key employees are more likely to overcome financial crises. The review emphasizes the importance of a holistic approach, combining financial relief, strategic leadership, and organizational resilience, for long-term SME recovery. The findings suggest avenues for future research on the interaction of these factors and their context-specific impacts.